2017
DOI: 10.1111/gcb.13628
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond presence and absence when examining changes in species distributions

Abstract: Species distributions are often simplified to binary representations of the ranges where they are present and absent. It is then common to look for changes in these ranges as indicators of the effects of climate change, the expansion or control of invasive species or the impact of human land-use changes. We argue that there are inherent problems with this approach, and more emphasis should be placed on species relative abundance rather than just presence. The sampling effort required to be confident of absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Quantifying shifts in species range boundaries is an important priority for species redistribution science (Bonebrake et al., ), yet difficulty identifying ranges edges from observational data make distinguishing shifts problematic (Ashcroft et al., ). For example, range boundaries determined directly from occurrence data are sensitive to sampling intensity (Brown et al., ), and variation in sampling effort through time can lead to incorrectly inferring range edge shifts (Bates et al., ; Hassall & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying shifts in species range boundaries is an important priority for species redistribution science (Bonebrake et al., ), yet difficulty identifying ranges edges from observational data make distinguishing shifts problematic (Ashcroft et al., ). For example, range boundaries determined directly from occurrence data are sensitive to sampling intensity (Brown et al., ), and variation in sampling effort through time can lead to incorrectly inferring range edge shifts (Bates et al., ; Hassall & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mapped indices of habitat suitability have previously been used to identify species core habitats (Hill, Tobin, Reside, Pepperell, & Bridge, ), but are rarely used to identify shifts in the range boundaries of marine species (but see Robinson, Gledhill, et al., ). Combining spatial predictions of species’ probability of occurrence from SDMs with sampling effort information has recently proved useful for identifying range boundaries for terrestrial species based on minimum relative abundance values (Ashcroft et al., ). When sampling effort is unknown, independent species occurrence data may be compared with spatial predictions from SDMs to define range boundaries or habitat edges in terms of a threshold probability of occurrence or a minimum habitat suitability value (Champion, Hobday, Zhang, Pecl, & Tracey, ).…”
Section: Introductionmentioning
confidence: 99%
“…This measure provides an estimate of variation explained between abundance and suitability. Lastly, previous studies have suggested that abundance–suitability relationships may be difficult to detect if variance in abundance estimates is too low (Ashcroft et al, ). That is, low variance and background noise in population abundance estimation could lead to type II errors.…”
Section: Methodsmentioning
confidence: 99%
“…This would be an important step forward to investigate macroecological patterns (McGill & Collins, ), such as species abundance distributions (McGill et al, ; Xiao, O'Dwyer, & White, ), biomass distribution (Hatton et al, ) or range size–abundance relationships (Gaston et al, ). Understanding the spatial patterns of abundance would allow conservation biologists to identify regions within species distributions where viability is low (Di Marco et al, ; Hilbers et al, ) and contribute to forecasting the responses of species to climate change, assuming space for time substitution as done in species distribution modelling (Ashcroft et al, ). Finally, estimates of species abundance over large geographical scales and for multiple species would permit description of the change in a number of biodiversity measures (e.g., heterogeneity indices, functional or phylogenetic diversity metrics weighted by species relative abundance) over time and space (Schipper et al, ).…”
Section: Introductionmentioning
confidence: 99%